STRATEGI PENGEMBANGAN BUDAYA MUTU DI SEKOLAH DASAR - Supriyanti, Yeti; Edi Rohyadi; Erwin Salpa Riansi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Quality culture in primary schools is an essential element in ensuring the sustainability of education quality. This research aims to identify key strategies in developing a culture of quality in primary schools through a literature review approach. The article analyzes several relevant literature sources, including indexed journals, academic books and research reports. The results show that strengthening the school's vision and mission, empowering teachers and staff, collaborating with parents and the community, innovating technology-based learning, contextualized learning, and the quality of the principal's leadership are effective strategic steps. In addition, the integration of local values such as gotong royong is a unique strength in supporting a culture of quality in the Indonesian context. Despite challenges such as limited resources and resistance to change, great opportunities exist through government policy support and the development of educational technology. This research provides theoretical and practical insights that can be adapted by primary schools to create a sustainable culture of quality.